2020
DOI: 10.2196/19104
|View full text |Cite
|
Sign up to set email alerts
|

Approaches Based on Artificial Intelligence and the Internet of Intelligent Things to Prevent the Spread of COVID-19: Scoping Review

Abstract: Background Artificial intelligence (AI) and the Internet of Intelligent Things (IIoT) are promising technologies to prevent the concerningly rapid spread of coronavirus disease (COVID-19) and to maximize safety during the pandemic. With the exponential increase in the number of COVID-19 patients, it is highly possible that physicians and health care workers will not be able to treat all cases. Thus, computer scientists can contribute to the fight against COVID-19 by introducing more intelligent sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 83 publications
0
104
0
1
Order By: Relevance
“…In the face of growing pressure on limited health care resources, the use of AI-driven techniques to aid in diagnosis, surveillance, finding therapeutics, and public health decision making may help improve the efficiency and effectiveness of human efforts to combat the pandemic. Another recently published review found that AI could contribute to the prevention and control of the spread of COVID-19 via several important approaches: detecting suspected cases, large-scale screening, monitoring, determining interactions with experimental therapies, pneumonia screening, using the Internet of Intelligent Things for data and information gathering and integration, allocating resources; making predictions, models, and simulations; and using robotics for medical quarantine [ 71 ]. We hope that our rapid review can help highlight additional areas for more robust AI applications and studies in the later phases of the ongoing pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of growing pressure on limited health care resources, the use of AI-driven techniques to aid in diagnosis, surveillance, finding therapeutics, and public health decision making may help improve the efficiency and effectiveness of human efforts to combat the pandemic. Another recently published review found that AI could contribute to the prevention and control of the spread of COVID-19 via several important approaches: detecting suspected cases, large-scale screening, monitoring, determining interactions with experimental therapies, pneumonia screening, using the Internet of Intelligent Things for data and information gathering and integration, allocating resources; making predictions, models, and simulations; and using robotics for medical quarantine [ 71 ]. We hope that our rapid review can help highlight additional areas for more robust AI applications and studies in the later phases of the ongoing pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…PCGs can also be plotted based on the NumPy array files for ease of visualization and analysis. These data can also be used in the future for research related to diagnosis and prognosis, such as use of machine learning algorithms [ 24 , 44 ]. The device may also have educational value as a teaching aid for medical students.…”
Section: Discussionmentioning
confidence: 99%
“…RGB cameras can conduct and analyze respiratory measurements of suspected individuals with the use of AI detection algorithms. [4][5][6] Similar applications were used in China which provided data on individual movement and diagnosis to a central database analyzed by an AI algorithm which issued a color code to guide movement restrictions. 7 Thousands of schools across the world remain closed due to ongoing threat of COVID-19 transmission among students.…”
Section: Case For Artificial Intelligence and Industry 40 Technologiesmentioning
confidence: 99%